2021
DOI: 10.1038/s41598-021-00543-9
|View full text |Cite
|
Sign up to set email alerts
|

A pathophysiological model of gait captures the details of the impairment of pace/rhythm, variability and asymmetry in Parkinsonian patients at distinct stages of the disease

Abstract: Locomotion in people with Parkinson’ disease (pwPD) worsens with the progression of disease, affecting independence and quality of life. At present, clinical practice guidelines recommend a basic evaluation of gait, even though the variables (gait speed, cadence, step length) may not be satisfactory for assessing the evolution of locomotion over the course of the disease. Collecting variables into factors of a conceptual model enhances the clinical assessment of disease severity. Our aim is to evaluate if fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
1
10
0
2
Order By: Relevance
“…In addition, we included a set of clinical and wearable sensor-based features descriptive of gait spatio-temporal aspects (i.e. 6MWT score, duration of stride, step, single support and double support phases) and gait quality (i.e., movement intensity and smoothness, stride/step regularity and variability, gait symmetry, and local dynamic instability) 25 27 , which are known to be impaired in PwND 3 , 19 , 28 32 . Alterations in gait spatio-temporal parameters have been well-documented in MS 33 , PD 34 and ST 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we included a set of clinical and wearable sensor-based features descriptive of gait spatio-temporal aspects (i.e. 6MWT score, duration of stride, step, single support and double support phases) and gait quality (i.e., movement intensity and smoothness, stride/step regularity and variability, gait symmetry, and local dynamic instability) 25 27 , which are known to be impaired in PwND 3 , 19 , 28 32 . Alterations in gait spatio-temporal parameters have been well-documented in MS 33 , PD 34 and ST 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the step and stride times, the respective coefficients of variation were added to the dataset, as measures of step and stride variability, which are usually higher in PwND compared to healthy subjects 75 . Then, a set of 18 metrics was computed, from all trunk acceleration components (antero-posterior, medio-lateral and vertical), to provide information about gait quality domains (i.e., intensity, regularity, symmetry, stability, and smoothness) proposed by previous literature 27 32 . Gait intensity was quantified through the root mean squared value of the acceleration 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, specific assessments to determine PD progression are essential (Marras et al, 2002). Gait analysis has been proved effective to establish PD progression according to recent studies (Godi et al, 2021;Varrecchia et al, 2021;Vila et al, 2021), which have identified several spatiotemporal and kinematic parameters capable of differentiating PD stages. However, functional ability includes other motor skills indicators of static balance, such as sitting down, getting up, or turning around, and the risk of falling in this population (Pelicioni et al, 2019;Muñoz-Bermejo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing gait kinematic variables related to the stages of PD evolution has lately been the object of investigation in several centers around the world, whether to identify different gait patterns between healthy people and people with the disease ( 56 ) or to identify more sensitive gait measures that discriminate stages of PD ( 57 ), or to analyze gait patterns about early (I-II) and intermediate (III-IV) stages, according to the Hoehn and Yahr scale (HY) ( 58 ). Through advanced technological resources such as sensors attached to the body and three-dimensional gait analysis platforms, these studies could distinguish specific critical points of assessment at each stage of PD, such as asymmetry for stage I, gait velocity for stage II and gait times, balance and stride for stage III ( 57 ), reinforcing that the association of spatiotemporal gait variables can better help the understanding of subtle changes between the stages of disease evolution ( 56 ). Postural instability interferes negatively in several gait parameters, as these variables worsen when balance deteriorates ( 58 ).…”
Section: Discussionmentioning
confidence: 99%